Inverse Analyses with Model Reduction Proper Orthogonal Decomposition in Structural Mechanics - Buljak, Vladimir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
In this self-consistent monograph, the author gathers and describes different mathematical techniques and combines all together to form practical procedures for the inverse analyses. It puts together topics coming from mathematical programming, with soft computing and Proper Orthogonal Decomposition, in order to show, in the context of structural analyses, how the things work and what are the main problems one needs to tackle. Throughout the book a number of examples and exercises are worked out in order to make reader practically familiar with discussed topics.
Inverse analyses -- Optimization algorithms -- Proper Orthogonal Decomposition and Radial Basis Functions for fast simulations -- Modern approach to inverse analyses -- Numerical examples.
Keywords: Engineering; Computer simulation; Computer science; Engineering mathematics; Mechanical engineering; Engineering; Appl.Mathematics/Computational Methods of Engineering; Computational Science and Engineering; Simulation and Modeling; Structural Mechanics